A novel FGF23 mutation in hyperphosphatemic familial tumoral calcinosis and its deleterious effect on protein O-glycosylation - Zuo, Qingyao; Yang, Weili; Liu, Baoyue; Yan, Dong; Wang, Zhixin; Wang, Hong; Deng, Wei; Cao, Xi; Yang, Jinkui (Frontiers in Endocrinology, 2022)
Background: Hyperphosphatemic familial tumoral calcinosis (HFTC) is a rare disease characterized by hyperphosphatemia and ectopic calcification, predominantly at periarticular locations. This study was performed to characterize the clinical profile of tumoral calcinosis and to identify gene mutations associated with HFTC and elucidated its pathogenic role. Methods: The three subjects (two male and one female) were aged 30, 25 and 15 years, respectively. The clinical features, histopathological findings, and outcomes of three subjects with HFTC were retrospectively reviewed. The three subjects were analyzed for FGF23, GALNT3 and KL mutations. Function of mutant gene was analyzed by western blotting and wheat germ agglutinin affinity chromatography. Results: All subjects had hyperphosphatemia and elevated calcium-phosphorus product. Calcinosis positions included the left shoulder, left index finger, and right hip. Bone and joint damage were present in two cases and multiple foci influenced body growth in one case. The histopathological features were firm, rubbery masses comprising multiple nodules of calcified material bordered by the proliferation of mononuclear or multinuclear macrophages, osteoclastic-like giant cells, fibroblasts, and chronic inflammatory cells. The novel mutation c.484A>G (p.N162D) in exon 3 of FGF23 was identified in one subject and his family members. Measurement of circulating FGF23 in the subject confirmed low intact FGF23 and increased C-terminal fragment. In vitro experiments showed that the mutant FGF23 proteins had defective O-glycosylation and impaired secretion. Conclusion: We identified a novel FGF23 missense mutation, and confirmed its damaging role in FGF23 protein O-glycosylation. Our findings expand the current spectrum of FGF23 variations that influence phosphorus metabolism.